Augmenting Museum Communication Services to Create Young Audiences - Nechita, Florin; Rezeanu, Catalina-Ionela (MDPI AG, 2019)
The aim of this paper is to demonstrate how museums use Augmented Reality (AR) to enhance communication services with their audiences and attract new ones. Still, there is no definite answer to how young audiences perceive the educational effects of experiencing this augmented space of communication as an immersive medium. This study is based on a survey of 400 students after they visited an AR technology-enhanced exhibition held by a local history museum. Two stimulus–response marketing scale metrics, widely used to assess TV commercials, were adapted for AR experiences and validated. The mediation analysis revealed an intervening emotional mechanism, in which the multisensory AR experience has educational effects through entertainment and empathy. An improved stimulus–response empirical model is proposed, in which AR technologies, as environmental multisensory stimuli, produce cognitive responses through emotional immersion. The findings have significance in improving how museums encode their message using AR technologies as a secondary communication medium with young audiences. By using a widely tested scale for evaluating TV commercials adapted to measure AR experiences, this study could inform museum professionals and application developers to improve AR implementation solutions as service tools for enhancing user experience.
Keywords: augmented reality; SOCIAL SCIENCES::Social sciences::Education; empathy; engagement; entertainment; young audiences